Incorporation of SMA technologies in fashion underwear apparel - Laschuk, Tatiana (2008)
The experiment has as main goal identify consumer needs for underwear bra apparel that deserves singular research attention, in order to associate it with a smart technology, the Shape Memory Alloys (SMA) as well as with fashion design. The SMA will be incorporated to provide functional behaviour to the bra, besides physiological and psychological comfort in a manner to supply woman needs related to the bra performance. The SMA was blended with cotton to improve the processability of bra knitting structure construction. Through a heat treatment the SMA bra was shaped set on the desired shape design. After high heat treatment it can be incorporated in the bra between two layers of fabric to improve the bra touch. When contacted the woman breast, the SMA bra will recover its original shape, providing a better performance colving problems like wrinkle and deterioration behaviour, generated by the way the bra is stored, or submitted to washing or drying machine.